PVP/CA/ROSELLA CALYX EXTRACT COMPOSITE NANOFIBERS: ITS FABRICATION USING ELECTROSPINNING AND ITS APPLICATIONS AS WOUND DRESSING - NUR'AINI (NIM : 20214038), HANNY
Colonies of bacteria on a wound surface can cause infection and chronic wound. On the other hand, wound must quickly be healed to prevent disfunctionality of the skin. One way to prevent wound infection by bacteria is by using a wound dressing. Now, many researchers have produced wound dressings from fibers with small diameter (micrometers to nanometers), since these fibers mimic the structure of tissue that helps the wound healing process. In addition, bacteria can also be prevented by inserting anti bacterial content into the fiber membranes of wound dressings. This research reports the fibers membranes made from polyvinylpyrrolidone (PVP) and cellulose acetate (CA) polymers using electrospinning method. Roselle calyx extract (RCE) as an active anti-bacterial ingredient was composited into the polymers. PVP/CA/RCE composite fibers were electrospun with varying solution concentration and flowrate. A larger concentration of the RCE could reduce the average diameter of fibers and increase the pH of fibers. The obtained FTIR spectra indicated that the PVP/CA/RCE composite fibers contain functional groups of PVP, CA and RCE. Besides, a larger flowrate produced fibers with beads and larger average diameter. While from the degree of swelling and antibacterial activity tests, it was found that a smaller diameter of fibers results in a larger amount of swelling and a higher antibacterial activity.